SARS CoV-2 infection as a risk factor of preeclampsia and pre-term birth. An interplay between viral infection, pregnancy-specific immune shift and endothelial dysfunction may lead to negative pregnancy outcomes - Aleksander Celewicz; Marta Celewicz; Michał Michalczyk; Paula Woźniakowska-Gondek; Kamila Krejczy; Marcin Misiek; Rafał Rzepka (Annals of Medicine, 2023)
AbstractBackground Since SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) was first identified as the cause of Coronavirus disease 19 (COVID-19) it has caused over 649,147,421 infections and over 6,730,382 deaths worldwide. SARS-CoV-2 presents higher infectivity than other coronaviridae (MERS-CoV and SARS-CoV). Pregnant patients, according to previous studies are at high risk of severe COVID-19 course and negative pregnancy outcomes (pre-term birth, low birth weight, preeclampsia, operative delivery and ICU admission with need for mechanical ventilation).Methods In this review we focus on the pathophysiology of subcellular changes in COVID-19 and try bring to light the aspects that occur in physiological pregnancy that may cause higher risk of SARS-CoV-2 infection and severe COVID-19 course.Results Knowledge of potential interplay between viral infection and physiological changes in pregnancy may point us in the direction of future prophylaxis and treatment in this special population.Key MessagesSARS-CoV-2 having affinity to ACE-2 and causing it’s downregulation receptor may cause endothelial injury leading to compliment activation and formation of NETs, together with RAS dysregulation this may cause preeclampsia to develop in pregnant patients.PTB may occur in patients as an effect of SARS-CoV-2 infection in first or second trimester as an effect of TLR4 pathway dysregulation with lower levels of IFNβ.